Mechanism for cyclization reaction by clavaminic acid synthase. Insights from modeling studies. - Borowski, T; de Marothy, S; Broclawik, E; Schofield, C; Siegbahn, P (2007)
The mechanism of the oxidative cyclization reaction catalyzed by clavaminic acid synthase (CAS) was studied in silico. First, a classical molecular dynamics (MD) simulation was performed to obtain a realistic structure of the CAS-Fe(IV)=O-succinate-substrate complex; then potential of mean force (PMF) was calculated to assess the feasibility of the beta-lactam ring, more specifically its C4' corner, approaching the oxo atom. Based on the MD structure, a relatively large model of the active site region was selected and used in the B3LYP investigation of the reaction mechanism. The computational results suggest that once the oxoferryl species is formed, the oxidative cyclization catalyzed by CAS most likely involves either a mechanism involving C4'(S)-H bond cleavage of the monocyclic beta-lactam ring, or a biosynthetically unprecedented mechanism comprising (1) oxidation of the hydroxyl group of PCA to an O-radical, (2) retro-aldol-like decomposition of the O-radical to an aldehyde and a C-centered radical, which is stabilized by the captodative effect, (3) abstraction of a hydrogen atom from the C4'(S) position of the C-centered radical by the Fe(III)-OH species yielding an azomethine ylide, and (4) 1,3-dipolar cycloaddition to the ylide with aldehyde acting as a dipolarophile. Precedent for the new proposed mechanism comes from the reported synthesis of oxapenams via 1,3-dipolar cycloaddition reactions of aldehydes and ketones.